Modeling of electromagnetic wave penetration in a human head due to emissions from cellular phone - Ismail, Nurulhuda

(untitled)
In recent years, there has been an increasing public concern about possible health hazard resulting from exposure to electromagnetic (EM) waves. Much attention has been paid to the induced of SAR in the human head for exposure to EM waves emitted from commercial cellular phone antennas. Therefore, the computation of the electric fields and SAR generated by cellular phone inside a four-tissue phantom head model is presented in this paper. The phone was considered working at 900MHz to 1800MHz bands according to the Global System of Mobile Communication (GSM). The penetration of the E-fields and averaged SAR values in 1g and 10g of tissue were computed inside the model of human head using Finite Difference Time Domain (FDTD) technique. The E-fields and SAR are then evaluated using CST Microwave Studio as it capable to do an accurate 3D simulation. The CST Microwave Studio results show that magnitude of EM field decreases exponentially with the penetration distance at a rate specified by the attenuation constant, α. Besides, the SAR is affected by operational frequency of the phone and the distance of the antenna to the human head. An experimental technique on SAR distribution needs to be done to validate the results from simulation technique.